Predicting the effect of vaccination on the transmission dynamics of heartwater (Cowdria ruminantium infection) - O'Callaghan, C.J.; Medley, G.F.; Peter, T.F.; Mahan, S.M.; Perry, Brian D. (Elsevier, 1999)
A mathematical description of the transmission dynamics of the tick-borne infection Cowdria ruminantium in commercial beef enterprises in Zimbabwe was used to consider the potential impact of a candidate vaccine to prevent heartwater. The important characteristics of the vaccine were (1) a delay in development of full protection, (2) prvention of clinical disease but not of infection and (3) a waning period of protection in the absence of challenge. Three different scenarios in which the vaccine might be used were considered: prophylactically in susceptible cattle prior to the introduction of infection into a herd; in susceptible cattle in the face of an epidemic (i.e., when the infection is introduced and disease is first noticed); and at equilibrium (i.e., when parasite, vector and host have been co-existing for some time). The epidemic rise in infection was modelled assuming two different patterns (i.e., resulting from slow and fast increases in tick challenge). Vaccination (administered both in the face of an epidemic and prophylactically) reduced and delayed the peak of the epidemic. With insufficiently frequent revaccination, this can result in the epidemic occurring during a period of susceptibility, so that the benefit derived from a more-efficacious vaccine is lower than that from a less-efficacious vaccine. A vaccine of only 30 percent or 50 percent efficacy (if given to the whole herd) can have important effects on both morbidity and mortality if administered with sufficient frequency. However, a highly efficacious vaccine (e.g., 90 percent) can have only minimal effect if revaccination occurs too infrequently - especially if the epidemic of disease occurs when tick challenge is high and vaccination-related immunity has waned. There was a fairly consistent pattern of decreasing returns on increasing protection, although this was reversed in the situation of annual vaccination undertaken prophylactically combined with an epidemic of infection that occurred when the tick challenge was relatively low. Vaccination in equilibrium situations was most beneficial at low and intermediate tick challenges. There was very little effect of vaccination in high-transmission areas regardless of vaccine efficacy and/or frequency of revaccination because most animals were infected during periods of innate or maternally derived immunity (i.e., under endemic stability). The results suggest that where relatively high tick challenge can be achieved and consistently maintained, vaccination may be used in susceptible herds to minimise losses in a policy of transition to endemic stability.